Reconstruction of the Midface and Palate - Bender-Heine, Adam; Wax, Mark K. (Seminars in Plastic Surgery, 2020)
The midface is a complex anatomic structure that is fundamental to many physiologic and homeostatic functions. It may be involved in many pathologic processes that require partial or complete removal. When this happens, reconstruction is mandatory to improve cosmetic outcome with its effect on social interaction as well as to provide an opportunity for complete orodental rehabilitation with restoration of all physiologic functions. This article will review the different reconstructive options available for complex defects of the maxillofacial complex. It will highlight the surgical options available to maximize functional restoration. Finally, it will discuss computer modeling to optimize reconstructive planning.
Keywords: free tissue transfer; surgical reconstruction; maxilla; maxillofacial reconstruction; dental rehabilitation